A Case of Identity for NLMS and Kaczmarz Algorithms - Muhammad Yasir Siddique Anjum (Universitas Islam Sultan Agung, 2022)
In this paper, we will demonstrate, by employing basic linear algebra, that two seemingly disconnected algorithms, the Kaczmarz algorithm, familiar to mathematics community as an iterative solver of linear systems, and the Normalized LMS (NLMS) algorithm, known to the signal processing community as a self-learning adaptive filter, are identical.